The Caprellidea (Crustacea: Amphipoda) from Mauritius Island, Western Indian Ocean - Guerra-García, José M. (Zootaxa, 2003)
The caprellidean fauna of Mauritius was investigated. Sixteen stations were selected around the island and different substrata (including algae, seagrass, sponges, hydroids, ascidians, echinoderms, encrusted dead corals, coral rubble, fine and coarse sediments) were sampled. The study reports seven species in six genera, five of which are new records for the island and one,Metaprotella mauritiensis is described as new to science. Metaprotella sandalensis Mayer, 1898 was the most common species in the coral reef system surrounding Mauritius.